Mamíferos de un agropaisaje de palma de aceite en las sabanas inundables de Orocué, Casanare, Colombia (2016)
The llanos region in eastern Colombia exhibits great biodiversity, and is being threatened by agro-industrial processes such as oil palm plantations. However, information about the mammals associated with these landscapes is very limited. We measured richness and capture frequencies of medium and large sized mammals using camera traps in an oil palm plantation and surrounding natural ecosystems, in the seasonally flooded savannas of the Department of Casanare, Colombia. We identify 16 medium to large mammals, and two species of mice, with a survey effort of 3937 camera/days. Capture frequencies varied according to the land cover type. All species were present in the gallery (riparian) forest. Nine species were also detected inside the oil palm plantation and six in savannas. The mammals we found in the plantation were mainly mesopredators and generalist species, while the mammals detected in forest have more restricted diets. We discuss the importance of the gallery forests and artificial lagoons as landscape tools that could enhance diversity in these agro-ecosystems.